Transformasi Nilai Rumah Adat Tongkonan Dalam Penyelenggaraan Pemerintahan Tana Toraja - Bakhtiar, Dr. Bakhtiar; Sudirman, Muh.; Sesilia Mangori, Febby (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2024)
This study aims to determine (1) the values contained in the Tongkonan traditional house (2) the form of transformation of the values of the Tongkonan traditional house in administering government in Tana Toraja Regency (3) supporting factors and inhibiting factors for the transformation of the values of the Tongkonan traditional house in administering government in Tana Toraja Regency. This research is a qualitative research. The types and sources of data used in this study are primary data sources and secondary data sources. Data collection techniques through observation techniques, interviews and documentation.The results of this study indicate that (1) The values contained in the Tongkonan traditional house are religious values, social values, political values, moral values, and cultural values (2) The Tana Toraja district government fulfills the community's needs in the fields of administration and civil registration in accordance with current procedures and laws. (3) Settlement of disputes in the community is resolved in an authorized institution (police), the government also involves the customary government in helping resolve land disputes. (4) The form of transformation of the values of the Tongkonan traditional house in the administration of government is that the Tana Toraja district government makes activities related to the values of the Tongkonan traditional house, for example social activities, community service, and cultural performances. The government also supports traditional traditions in Tana Toraja, and involves traditional institutions in administering government. (5) The factors that influence the transformation of the value of the Tongkonan traditional house in the governance of Tana Toraja Regency are divided into supporting and inhibiting factors. As for the supporting factors, namely the values in the Tongkonan traditional house are in harmony with the way of government in Tana Toraja, there are villages in Tana Toraja that still adhere to the traditions and customs of Tana Toraja. As for the inhibiting factors, namely the factor of religion, the times and the establishment of formal government institutions that run the government in Tana Toraja today.